Crowdsourcing Change: An Analysis of Twitter Discourse on Food Waste and Reduction Strategies - Annie R. Specht; Emily B. Buck (Journal of Applied Communications, 2019)
Food waste has emerged as a major issue in the United States as the nation collectively sends more than 133 billion pounds of food to its landfills every year. In September 2015, the USDA and EPA announced an initiative to cut U.S. food waste in half by 2030. Between 2015 and 2016, nearly 100,000 posts about food waste have been published on Twitter, a microblogging platform that has been a hub of “slacktivism” since its inception in 2006. Using a conceptual framework of social cognitive theory, online activism, and crowdsourcing, we analyzed food waste conversation participants’ demographics, online communities, and proposed solutions. Data analysis was conducted with listening software Sysomos MAP and a qualitative content analysis of conversation content. The analysis revealed that more than 2,000 U.S. users engaged in the conversation, forming four discrete conversation communities led by influencers from government, news media, and environmental organizations. Proposed solutions to the food waste crisis included domestic or household behavior change, food-waste diversion and donation, recycling and upcycling, consumer education, and governmental action and policy. We recommend using Twitter to mine, test, and deploy solutions for combating food waste; engage with influential users; and disseminate materials for further research into the behavioral implications of online activism related to food waste.
Keywords: Social media; activism; food waste; influencer; crowdsourcing